Keterbukaan Perdagangan dan Emisi CO2: Studi Empiris Tingkat Provinsi di Indonesia - Nanda Puspita; Djoni Hartono (Jurnal Wilayah dan Lingkungan, 2021)
There are pros and cons to the results of previous studies regarding the relationship between trade openness and the environment, prompts a deeper investigation of the mechanisms of trade in influencing the environment. This study aims to examine the relationship between trade openness and the level of per capita CO2 emissions in Indonesia during the period 2010-2018, through three mechanisms, namely scale effects, technique effects and composition effects, as well as comparing the results of using two types of trade intensity measures, namely trade share and composite trade share. The analysis was conducted at the provincial level and using the random & fixed effects panel estimation method. The results of the study show that trade openness has a positive relationship with the level of per capita CO2 emissions in Indonesia, with the scale effect being more dominant than the technique effect. Furthermore, the composition effect caused by the high capital-labour ratio in a region is the main contributor to the increase in emissions compared to the composition effect due to trade activities induced by the comparative advantage between regions which have negative elasticity. Moreover, the composite trade share index is able to explain trade openness more comprehensively than the trade share.